A human microprotein that interacts with the mRNA decapping complex - D'Lima, Nadia G; Ma, Jiao; Winkler, Lauren; Chu, Qian; Loh, Ken H; Corpuz, Elizabeth O; Budnik, Bogdan A; Lykke-Andersen, Jens; Saghatelian, Alan; Slavoff, Sarah A (Nature chemical biology, 2017)
Mass-spectrometry-based proteomics led to the identification of NoBody, a microprotein translated from LINC01420 RNA, which interacts with enhancer of decapping 4 (EDC4) and negatively regulates 5′-to-3′ mRNA decay. Proteomic detection of non-annotated microproteins indicates the translation of hundreds of small open reading frames (smORFs) in human cells, but whether these microproteins are functional or not is unknown. Here, we report the discovery and characterization of a 7-kDa human microprotein we named non-annotated P-body dissociating polypeptide (NoBody). NoBody interacts with mRNA decapping proteins, which remove the 5′ cap from mRNAs to promote 5′-to-3′ decay. Decapping proteins participate in mRNA turnover and nonsense-mediated decay (NMD). NoBody localizes to mRNA-decay-associated RNA–protein granules called P-bodies. Modulation of NoBody levels reveals that its abundance is anticorrelated with cellular P-body numbers and alters the steady-state levels of a cellular NMD substrate. These results implicate NoBody as a novel component of the mRNA decapping complex and demonstrate potential functionality of a newly discovered microprotein.